ANALISIS PERBUATAN YANG DAPAT DIKENAKAN SINGER MENURUT HUKUM ADAT KALIMANTAN TENGAH DALAM PERSPEKTIF HUKUM PERDATA - Putri, Yoke Shintia; Joni; Tasrifinoor (The Juris, 2024)
The customary law still in effect in Central Kalimantan, particularly among the Dayak Ngaju tribe, serves as a means of social control and governance. This study employs normative legal research methods and qualitative research types with a statutory approach. In Dayak Ngaju customary law, "Singer" refers to a sanction in the form of a fine. Established in 1984 during the great Tumbang Anoi meeting, the Singer was intended to put an end to hostile traditions between Dayak sub-tribes, such as headhunting and slavery. The fine acts as a form of atonement to avoid divine retribution and the wrath of nature's guardians. The primary objective of Singer is to deter individuals, making them aware of their wrongdoing and preventing recurrence. Offenses subject to customary sanctions include environmental destruction, violations of social norms, criminal acts, infringements on customary rights, and disobedience to customary law. Customary fines may consist of goods, animals, or money, often accompanied by rituals to restore communal balance. For legal certainty, the regulation of the execution of Dayak customary court decisions should be codified into clear written law, specifying the authorities responsible for enforcement and penalties for those who fail to pay the Singer.